Pengaruh brand personality, WOM, dan price terhadap brand awareness dan purchase decision pengguna Shopee - Carolina, Valentina; Setyawan, Ignatius Roni (Universitas Tarumanagara, 2025)
This research aims to analyze the influence of brand personality, word of mouth, and price factors on brand awareness, as well as their impact on Shopee users' purchase decisions. Using a correlational non-experimental quantitative approach, this research involved 110 respondents who were active Shopee users and had made transactions. Primary data was obtained through a 1-5 Likert scale-based questionnaire which was distributed online and analyzed using the SmartPLS application. The results of the analysis showed that brand personality and word of mouth had a positive and significant influence on brand awareness, while price did not have a significant influence. Although brand personality and word of mouth can influence consumer interest, they do not have a direct significant influence on purchase decisions. On the other hand, price has a positive and significant influence on purchase decisions, indicating that competitive prices directly influence consumer preferences. Brand awareness functions as an important mediator, strengthening the influence of brand personality and word of mouth on purchase decisions. In conclusion, Shopee can implement two main strategies: increasing brand awareness through brand personality and word of mouth to build long-term loyalty, or using pricing strategies to increase sales quickly but short term. These findings provide insights for e-commerce platforms in designing more effective marketing strategies to maintain competitiveness and increase customer satisfaction in a dynamic market. Penelitian ini bertujuan untuk menganalisisa pengaruh faktor brand personality, word of mouth, dan price terhadap brand awareness, serta dampaknya pada purchase decision pengguna Shopee. Dengan menggunakan pendekatan kuantitatif non-eksperimental korelasional, penelitian ini melibatkan 110 responden yang merupakan pengguna aktif Shopee yang telah melakukan transaksi. Data primer diperoleh melalui kuisioner berbasis skala likert 1-5 yang disebarkan secara online dan dianalisis menggunakan aplikasi SmartPLS.Hasil analisis menunjukkan bahwa brand personality dan word of mouth memiliki pengaruh positif dan signifikan terhadap brand awareness, sedangkan price tidak memberikan pengaruh signifikan. Meskipun brand personality dan word of mouth dapat memengaruhi minat konsumen, keduanya tidak memiliki pengaruh signifikan langsung terhadap purchase decision. Sebaliknya, price memiliki pengaruh positif dan signifikan terhadap purchase decision, menunjukkan bahwa harga kompetitif langsung memengaruhi preferensi konsumen. Brand awareness berfungsi sebagai mediator penting, memperkuat pengaruh brand personality dan word of mouth terhadap purchase decision.Kesimpulannya, Shopee dapat menerapkan dua strategi utama: meningkatkan brand awareness melalui brand personality dan word of mouth untuk membangun loyalitas jangka panjang, atau menggunakan strategi harga untuk meningkatkan penjualan secara cepat tetapi jangka pendek. Temuan ini memberikan wawasan bagi platform e-commerce dalam merancang strategi pemasaran yang lebih efektif guna mempertahankan daya saing dan meningkatkan kepuasan pelanggan di pasar yang dinamis.